2021
DOI: 10.1088/1755-1315/687/1/012191
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption, emission and economy analysis of fuel cell vehicle in China

Abstract: Compared with internal combustion engine vehicles and electric vehicles, the advantages of fuel cell vehicles are still in a qualitative stage, and there is no clear quantitative analysis. In this paper, the energy consumption and emission results of twelve different hydrogen paths are calculated through the secondary modeling in GREET, and the total energy consumption and emissions of fuel cell vehicles, internal combustion engine vehicles, and electric vehicles are obtained. The results show that electric ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…An alternative eco-friendly technology, fuel cells vehicles (FCVs), may be more appealing to consumers with range anxiety or ones who cannot charge their vehicle from home [116]. FCVs can become a major competitor to BEVs, as they have lower life-cycle emissions, run higher ranges, and require a shorter time to refuel [117]. In masculine cultures, on the other hand, marketers should pay attention to men's attraction to state-of-the-art technologies.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative eco-friendly technology, fuel cells vehicles (FCVs), may be more appealing to consumers with range anxiety or ones who cannot charge their vehicle from home [116]. FCVs can become a major competitor to BEVs, as they have lower life-cycle emissions, run higher ranges, and require a shorter time to refuel [117]. In masculine cultures, on the other hand, marketers should pay attention to men's attraction to state-of-the-art technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the economics of fuel cell vehicles has thus become particularly important [31]. The fuel cell industry in China is in its initial stages, and research on the life cycle evaluation of FCEVs is still immature [32][33][34][35]. This paper tests and analyses the differences in control strategies and fuel economy of two fuel cell vehicles, test vehicles A and B, to provide reference data for studying the economics of the operational phase of an FCEV, which consists of proton exchange membrane fuel cell (PEMFC) in China.…”
Section: Subitem Percentage (%)mentioning
confidence: 99%
“…It must be said that carbon accounting is an important component of achieving carbon peaking and carbon neutrality. Through researching the articles published in the research field in the past ten years at home and abroad, it was found that fewer studies used empirical methods to study the influence of CAID [5]. At this stage, China has no relevant theoretical system to effectively guide and constrain Chinese listed companies, resulting in low overall disclosure level.…”
Section: Introductionmentioning
confidence: 99%